Using transcendental phenomenology to explore the social jugaads of transacting money post demonetisation in India. (20th June 2019) - Singh, Shaili; Sharma, Abhishek; Nandi, Shirsendu
The present study investigates the post effects of demonetisation that occurred in India on November 8, 2016, through the first-person point of view experience. The paper analyses individual and collective construction of social jugaad or innovative solutions that local people adopted for depositing and withdrawing the money alone or with the help of others. The region of study is a small tier-2 city of Rohtak, in the state of Haryana, which is in the proximity of the National Capital Region of the country. The study applies transcendental phenomenology to capture the essence of individual experiences and assess the universal meanings of the phenomenon. This research could be useful in understanding the possible ways in which people would react to such a step of the government and provides information for policymaking, aimed at addressing currency disposal behaviours.